STRATEGI UNTUK MENINGKATKAN KOMPETENSI DAN DAYA SAING ORGANISASI - Pasaribu, Petty Herawati; Faeni, Dewi Puspaningtyas (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Human resource (HR) training and development is a strategic aspect that is crucial in enhancing individual competencies while supporting organizational competitiveness. In an era of globalization filled with challenges, the need for adaptive, innovative, and productive HR is increasingly critical. Training refers to short-term learning processes aimed at improving specific skills, while development focuses on the long-term growth of individuals in a professional context. The importance of HR training and development lies in its role in strengthening employee productivity, driving innovation, and ensuring the achievement of an organization's strategic objectives. Skilled employees, whose knowledge is continuously updated, are better equipped to adapt to changes in technology and the market. Additionally, effective training improves job satisfaction, loyalty, and motivation, ultimately contributing to the overall success of the organization. The implementation strategy for training and development requires a systematic approach, starting from identifying training needs, designing relevant programs, to evaluating training outcomes. Technology-based approaches such as e-learning and online training platforms have become popular choices, given their flexibility in reaching a wide range of employees. Furthermore, collaboration with educational institutions, project-based training, and mentoring have proven effective in enhancing employee competencies